Human Resources Management and Development in the Organizations - Contemporary Trends and Challenges - Atanassova, Margarita (Research Papers, 2019)
The main purpose of this article is to present current trends in the human resources management and development and to systematize key challenges in this area. The research methodology includes the following main stages: presentation of transformations in approaches to labor and contemporary global trends in training, development and performance evaluation; analysis of the spread of selected contemporary practices in the human resources management in companies in Bulgaria; outlining major challenges to organizational management activities in this area. The findings highlight a number of challenges for the management and development of people in organizations, among which stand out: the internal mobility of the workforce in companies and leadership skills for effective feedback and for competences development of people in the teams.